IUCN-CITES match is not required: A reply to Gorobets - Michal Berec (Elsevier, 2021)
Gorobets (Wild fauna conservation: IUCN-CITES match is required. Ecol. Indic. 112 (2020), 106091) has recently proposed to increase the effectiveness of species protection by maximizing the overlap of the IUCN Red List and CITES Appendices. This would increase the number of animal species in CITES Appendices by 229%. We consider this unnecessary or even counterproductive, because these lists are based on different protection rules and objectives.